Analisis Berbagai Faktor yang Berkontribusi terhadap Niat Berpindah Kerja Karyawan di PT Daya Surya Sejahtera Ponorogo - Yuvi Safitri; Umi Farida; Fery Setiawan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to identify the influence of job satisfaction, occupational health and safety (OHS), and work stress on turnover intention among employees of PT. Daya Surya Sejahtera Ponorogo. The high turnover rate is a phenomenon that has the potential to hamper the smooth operation of the company and increase the costs of recruiting and training new employees. Therefore, understanding the factors that influence the intention to leave the company is important in order to maintain workforce stability and productivity. This study uses a quantitative approach with a survey method through distributing questionnaires to respondents. The sampling technique used is simple random sampling, with the Slovin formula, resulting in 72 respondents from a total population of 250 employees. The data obtained were then analyzed using multiple linear regression methods with the help of SPSS version 25 software. The results of the analysis show that the three independent variables, namely job satisfaction, OHS, and work stress, simultaneously have a significant effect on turnover intention. Partially, job satisfaction and OHS have a negative effect on turnover intention, meaning that the higher the job satisfaction and good OHS implementation, the lower the employee's intention to leave the company. Conversely, job stress showed a positive effect, meaning that the higher the level of job stress, the greater the employee's intention to resign. This finding indicates the importance of management attention to working conditions, employee well-being, and stress management in the workplace. Companies are advised to consider providing competitive compensation, creating a healthy and safe work environment, and providing career development paths as strategies to sustainably reduce employee turnover intentions.